2017
DOI: 10.1051/0004-6361/201630099
|View full text |Cite
|
Sign up to set email alerts
|

Mass retention efficiencies of He accretion onto carbon-oxygen white dwarfs and type Ia supernovae

Abstract: Context. Type Ia supernovae (SNe Ia) play a crucial role in studying cosmology and galactic chemical evolution. They are thought to be thermonuclear explosions of carbon-oxygen white dwarfs (CO WDs) when their masses reach the Chandrasekar mass limit in binaries. Previous studies have suggested that He novae may be progenitor candidates of SNe Ia. However, the mass retention efficiencies during He nova outbursts are still uncertain. Aims. In this article, we aim to study the mass retention efficiencies of He n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 58 publications
(81 reference statements)
3
39
0
Order By: Relevance
“…As well, masstransfer rates based on the latter M-R relation, excellently agree with those, based on M-R relation for finite, but low, entropy WDs suggested by Bildsten et al (2006). 1 We remind also that, as found first by Nomoto (1982) and, most lately, e.g., in our Paper I and by Brooks et al (2015); Wu et al (2017), He-burning may occur in the following regimes (in the order of increasing accretion rate M accr ).…”
Section: Introductionsupporting
confidence: 86%
“…As well, masstransfer rates based on the latter M-R relation, excellently agree with those, based on M-R relation for finite, but low, entropy WDs suggested by Bildsten et al (2006). 1 We remind also that, as found first by Nomoto (1982) and, most lately, e.g., in our Paper I and by Brooks et al (2015); Wu et al (2017), He-burning may occur in the following regimes (in the order of increasing accretion rate M accr ).…”
Section: Introductionsupporting
confidence: 86%
“…We note in passing that He retention efficiencies have also been published by Piersanti et al (2014) and Wu et al (2017). As the former extend only up to a WD mass of ≈ 1 M , they cannot be applied in the evolution up to explosion.…”
Section: Mass Retention Efficiencymentioning
confidence: 91%
“…Their calculated values of η He are generally between those of Kato & Hachisu (2004) and Wang et al (2015). Assuming that there are supper-Eddington winds during multi-cycle He-shell flashes, Wu et al (2017) also calculated the values of η He , and found them to be lower than those in Kato & Hachisu (2004).…”
Section: Non-magnetic Wdsmentioning
confidence: 95%